Spatial and Regional Analysis of Precipitation Trend over Iran in the Last Half of Century - Mohammad Nazeri Tahrudi (مجله آب و خاک, 2017)
Introduction: Climate change has been one the most important subject in studies in the recent decades. Precipitation is an effective climatic parameter in the municipal and rural studies and in the industry, architecture, agriculture, climate and other fields. Trend analysis of average monthly and yearly rainfall investigated in many studies, but less researches probe regional rainfall analysis. In this study average yearly precipitation data measured at 31 synoptic stations of Iran in the period of 1961 to 2010 used to study regional variations of precipitation. In this order station divided to five regions by fuzzy clustering. Then, using the regional Kendall method, trend of precipitation investigated at five regions and all of Iran. Materials and Methods: Iran with an area of over 16480000 square kilometers is situated in the northern hemisphere and southwest of Asia. Almost all parts of Iran have four seasons. In general, a year can be divided into two warm and cold seasons. Iran with range annual precipitation of 62.1-344.8 mm is located between two meridians of eastern 44° and 64° and two orbits of northern 40° and 25°. In order to investigate trend of precipitation two Mann-Kendall and Regional Kendall tests used. Also to evaluate the regional trends the Fuzzy method applied to clustering the studied region. The classic form of Mann-Kendall test has been used in many studies. The null hypothesis (no trends) is accepted when , otherwise H0 is rejected and its opposite hypothesis, i.e. the existence of a trend is accepted (5, 13). To estimate regional trend, the mean S statistic of Regional Mann-Kendall introduced that was presented by Douglas et al (7). Fuzzy Clustering: Clustering the studied area was done using the Fuzzy clustering method. One of the first clustering methods that were based on the objective function and Euclidean distance was presented by Dunn in 1974 and then was generalized by Bezdak in 1981.The FCM clustering algorithm is modified type of K-Means clustering algorithm. This algorithm minimizes the variance of clusters (1). The assumption of this algorithm is that data are in a vector space and the objective of this algorithm is to minimize the sum of variance in the D v cluster. Results and Discussion: In this section the results of decreasing and increasing trend of annual precipitation of Iran can be observed in order to the data that recorded at provinces synoptic stations in the 1 and 5 percentage significance levels. Isfahan Synoptic station detected an increasing trend insignificant level of 5 percentages and the East Azerbaijan synoptic station followed a significant and severe decreasing trends. In order to investigate regional trend it is needed to use the clustering methods. After investigation the trend of mean annual precipitation at each station, the studied area was clustered using the Fuzzy clustering method and then the regional trend of Iran’s precipitation was evaluated. At first the number of different clusters investigated using the geographic properties and mean annual precipitation of the studied area and then with attention to the correlation of precipitation series in each cluster, five clusters selected to investigate the regional trend of precipitation. Overall the results showed that about 67 percentages of synoptic stations in center of provinces detected decreasing trend in the recent half century. Increasing the precipitation almost accrued in the center and northern part of Iran and other areas detected a decreasing precipitation trend in the studied data period that this subject is corresponded with Azerakhshi and et al (2). The observed trends over Iran and almost all stations and provinces were downward trend. This decreasing trend of precipitation also observed in Iran in the two past decades by Khalili et al (13). Conclusion: Result showed decreasing trend in the west, north of Iran at each station and regional scale. Results indicated also a significant downward trend at northwest, central and south-west of the country, non-significant downward trend in western of Iran and non-significant upward trends in northern regions and Caspian Sea margins in the regional analysis. The most decreasing trend of precipitation observed at the north west of Iran because of increasing temperature and climate changes in the recent years.